Hubungan Fungsi Perawatan Kesehatan Keluarga dengan Kadar Kolesterol Pasien Hiperkolesterolemia di Wilayah Kerja Puskesmas Andalas Padang Tahun 2013 : The Relationship between Family Health Care Function and Cholesterol Levels of Hypercholesterolemia Patients in the Working Area of Andalas Padang Health Center in 2013 - Irawati; Fitra Yeni (Fakultas Keperawatan Universitas Andalas, 2013)
Hypercholesterolemia be a risk factor for coronary heart disease and the number one cause of death. Controlling cholesterol is done by involving the family in carrying out the functions of family health care. The purpose of this study was to determine the most significant variables. This type of research is a descriptive analytic with cross sectional design. The research sites in the Work Area Health Center Andalas Padang with respondents 60 people. Bivariate analysis with the chi square test and multivariate analysis with regression logistic. The results showed a significant relationship between the functions of family health care practices in the implementation of diet p=0,004(p<0,05), physical activity and recreation p=0,002(p<0.05) with cholesterolemia levels, the the implementation of practice-based preventive treatment p=0,925(p>0.05). The most significant variables is function of family health care practices in the implementation of the diet p=0,007, OR=4,896 (95%CI=1,548-15,486). Suggested to the clinic in order to increase the frequency of home visits and advised the family to more active in implementing the functions of family health care.